New insights on the Early Pleistocene equids from Roca-Neyra (France, central Europe): implications for the Hipparion LAD and the Equus FAD in Europe. (March 2021) - Cirilli, Omar; Bernor, Raymond L.; Rook, Lorenzo
Abstract: We undertake a redescription of the equid sample from the Early Pleistocene of Roca-Neyra, France. This locality has been recently calibrated at the Pliocene/Pleistocene boundary (2.6 ± 0.2 Ma) and therefore it is of interest for the first appearance of the genus Equus and last appearance of hipparionine horses. The Roca-Neyra equid sample, re-analyzed herein using morphological, morphometrical, and statistical analyses, has revealed the co-occurrence of Plesiohipparion cf. ? P . rocinantis and Equus cf. E . livenzovensis . The analysis undertaken on several European, African, and Asian " Hipparion " sensu lato species from late Miocene to Early Pleistocene has revealed different remnant Hipparion lineages in the Plio-Pleistocene of Europe: Plesiohipparion, Proboscidippaion, and likely Cremohipparion . The discovery of the first European monodactyl horse, Equus cf. E . livenzovensis correlates Roca-Neyra with other 2.6 Ma European localities in Italy, Spain, and in the Khapry area (Azov Sea region). The morphological description of the Equus cf. E . livenzovensis lower cheek teeth has highlighted intermediate features between the North American Pliocene species Equus simplicidens and Early Pleistocene European Equus stenonis . Our study supports the hypothesis that E . livenzovensis is a plausible evolutionary predecessor for the Equus stenonis group. These observations underscore the importance of Roca-Neyra as an important locality for the last European hipparions and the first Equus in the Early Pleistocene of Europe.